Preparation and Electron-Beam Surface Modification of Novel TiNi Material for Medical Applications - Anikeev S. G.; Shabalina A. V. Anastasiya Valerjevna; Kulinich S. A. Sergei; Artyukhova N. V. Nadezhda Viktorovna; Korsakova D. R. Darjya Ruslanovna; Yakovlev E. V. Evgeny Vitaljevich; Vlasov V. A. Vitaliy Anatolievich; Kokorev O. V. Oleg Viktorovich; Khodorenko V. N. Valentina Nikolaevna (2021, 2021)
Title screen